A Case of Malignant Low Grade Endometrial Stromal Sarcoma and Review of The Literature - Amrish N Pandya; Arpita Nishal; Hemali Tailor (Medsci Publications, 2011)
Low grade endometrial stromal sarcoma is a rare pelvic malignancy that arises from the endometrium. This article describes the morphological features of one such tumour discovered as finding in a hysterectomy specimen of a 32-year lady with a clinical diagnosis of dysfunctional uterine bleeding with multiple fibroids. Morphological and immunohistochemical evaluations were performed and a final diagnosis of low grade endometrial stromal sarcoma was given. This report is aimed to present a case of endometrial stromal tumor because of its rare existence and difficulties in establishing histological diagnosis.